Analisis Pelaksanaan Program CSR PT Astra Agro Lestari Di Kelurahan Martajaya, Kabupaten Pasangkayu, Sulawesi Barat - Jihan Dzalfana; Lia Natalia Sonda; Nira Ramadhani; Novianti Dewi Lestari; Hikma; Sukri; Rachmad; Daswati (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Corporate Social Responsibility (CSR) is a legal and moral obligation for companies operating in the natural resource sector in Indonesia, as mandated by Law Number 40 of 2007 on Limited Liability Companies and Government Regulation Number 47 of 2012. This study aims to analyze the implementation of CSR programs by PT Astra Agro Lestari in Martajaya Village, Pasangkayu Regency, West Sulawesi. The research employs a qualitative descriptive approach, with data collected through interviews and direct observation involving company representatives, local government officials, and community beneficiaries. Data analysis was conducted using the interactive model of Miles and Huberman (1994), encompassing data reduction, data display, and conclusion drawing. The findings reveal that PT Astra Agro Lestari implements CSR through four main pillars: Astra Cerdas (education), Astra Sehat (health), Astra Kreatif (economy), and Astra Hijau (environment), across six assisted villages including Martajaya. The programs are designed through a participatory consultative approach, ensuring community involvement from planning to evaluation. Overall, the CSR implementation has provided tangible benefits to the local community and contributed to strengthening the harmonious relationship between the company and the surrounding population. However, continuous monitoring and adaptive evaluation are needed to ensure the long-term sustainability and effectiveness of these programs.